Optimization of Ni–Cr flux growth for hexagonal boron nitride single crystals - Hoffman, Timothy B.; Clubine, B.; Zhang, Y.; Snow, K.; Edgar, James H. (My University, 2014)
Hexagonal boron nitride (hBN) single crystals were grown using a Ni–Cr flux growth method. The crystallization cooling rate, soak temperature and soak time were controlled to determine their effect on crystal size and quality. A cooling rate of 2 °C/hr produced the best quality hBN crystals. The maximum crystal width increased with soak temperature from 1 mm at 1450 °C to 5 mm at 1700 °C. The crystal thickness decreased with soak temperature from 500 µm at 1500 °C to 40 µm at 1700 °C. A soak time of 24 to 48 h produced the maximum crystal thickness. X-ray diffraction and Raman spectroscopy confirmed that the crystals were highly ordered and of high purity.
Keywords: Nitrides; Semiconducting III-V materials; Single crystal growth; Growth from solutions; Crystal morphology